Critical information infrastructures security : 14th International Conference, CRITIS 2019, Linköping, Sweden, September 23-25, 2019, Revised selected papers /: 14th International Conference, CRITIS 2019, Linköping, Sweden, September 23-25, 2019, Revised selected papers. (2020) - Unknown
No abstract available